Non-invasive quantitative characterization of aortic valve tissue composition from computed tomography angiography improves patient risk stratification in transcatheter aortic valve implantation. (25th November 2020) - Grodecki, K; Tamarappoo, B.K; Huczek, Z; Jedrzejczyk, S; Cadet, S; Kwiecinski, J; Slomka, P; Rymuza, B; Filipiak, K.J; Dey, D
Abstract: Background: Computed tomography angiography (CTA) performed for procedural planning of transcatheter aortic valve implantation (TAVI) can be used for a more complete characterization of aortic valve tissue beyond calcium assessment. Combining quantitative data on both noncalcified and calcified tissues may improve differentiation of aortic stenosis (AS) subtypes and prognostication post-TAVI. Purpose: We sought to noninvasively assess aortic valve tissue composition with quantitative cardiac CTA in patients with AS and its prognostic vaalue in those who underwent TAVI. Methods: In 185 consecutive AS patients in a prospective registry who underwent cardiac CTA before TAVR and 90 matched controls with normal aortic valves, non-luminal aortic valve tissue were identified using semi-automated software as non-calcified (low-attenuation [−30 to 30 Hounsfield Units (HU)], fibro-fatty (31 to 130 HU), fibrous (131 to 350 HU) and calcified (>650 HU) tissue; with total tissue as (non-calcified + calcified components). Volumes of each component and composition [(tissue component volume/total tissue volume) ×100%] were quantified. The association of aortic valve composition and clinical outcomes post-TAVI including all-cause mortality was evaluated using Valve Academic Research Consortium (VARC)-2 definitions. Results: AS patients had greater aortic valve tissue volume (median 2000.2, vs 527.8 mm 3, p<0.001) with a higher calcified tissue composition (41.8% vs 3.4%, p<0.001) compared to controls. Total aortic valve tissue (noncalcified and calcified) volume yielded the highest area under the operating curve (AUC) for diagnosing severe AS (0.93, 95% CI:0.93–0.99) as compared to calcified tissue volume alone (0.87, 95% CI:0.81–0.94, p=0.002). Low-flow low-gradient AS was associated with increase in total tissue volume compared to controls (1515.3 vs 527.8 mm 3, p<0.001), with lower volumes of calcified tissue than high-gradient AS (412.5 vs 829.6 mm 3, p<0.001). Device success was achieved in 88% (164 of 185) patients and prevalence of moderate or severe paravalvular leak was 3.8%, however no differences between in aortic valve composition were observed in patients with and without device success. Early safety endpoints occurred in 16.1% (29 of 180) patients and 30-day all-cause mortality was 4.4%. Whereas only calcified tissue volume was related to VARC-2 early safety, AUC for prediction of 30-day mortality post-TAVI was 0.793 (95% CI:0.685–0.901) for total tissue volume and 0.776 (95% CI:0.676–0.876) for calcified tissue volume. Conclusions: Quantitative CTA assessment of aortic valve tissue volume and composition can improve identification of high-gradient AS and low-flow low-gradient AS patients referred for TAVI and predict 30-day mortality post-TAVI. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Heart, Lung, and Blood Institute (NHLBI)